IMPLEMENTATION OF E-GOVERNMENT IN PROCUREMENT OF GOODS AND SERVICES: STUDY: ELECTRONIC PROCUREMENT SERVICE OFFICE (LPSE) MEDAN CITY - H Silaban, Pantas; Fila Sari Saragih, Agitha; Peranginangin, Chandra; Manalu, Palti; F.D. Silalahi, Chandra (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
This study aims to find out how the process of implementing E-Government in the Procurement of Goods and Services at the Medan City LPSE Office and to find out the obstacles faced by the Medan City Electronic Procurement Service (LPSE) in carrying out their authority and the settlement pattern applied. The research method used in this study is to use a systematic review to examine issues related to travel risk and gender, while Pickering discusses the benefits of systematic reviews in research, especially for those who are completing a doctoral program. The research begins by setting search keywords, then searching data through a predetermined search engine application. The results of this study conclude that the implementation of e-government in the city of Medan can create a synergy between the community and the government, where the community can participate in building the city, while the government can channel their ideas